The desired role of strengthening the relationship between the private sector and Saudi universities in light of the Kingdom’s vision of the Kingdom 2030 - Alhowass, Hamad Khaled; Al-Osaimi, Ahmed Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to know the desired role to strengthen the relationship between the private sector and Saudi universities in light of the Kingdom’s 2030 vision. To achieve the aim of the study, the researcher used the descriptive survey approach and the questionnaire as a tool to collect data, and the study sample consisted of (746) individuals, including (627) leaders in universities, and (119) leaders in the private sector, and the results of the study showed that the study sample agreed to the role hoped for in strengthening the relationship. Between the private sector and Saudi universities in light of the Kingdom’s vision, where he obtained an overall average (3.07 out of 5). And that the most prominent features of the expected role of strengthening the relationship between the private sector and Saudi universities are the participation of private sector institutions in (Events organized by universities to connect their graduates to the labor market with an average of (3.45), meetings and workshops with universities with an average of (3.32), and the participation of some university professors in their boards of directors or advisors with an average of (3.29)). Private sector institutions benefit from their relationships with universities to develop their economic performance, and the contribution of private sector institutions by implementing training programs for university students in their various facilities, on average, and the contribution of private sector institutions in financing joint qualitative research with the Universities. The researcher recommends opening multiple communication channels between universities and private sector institutions to see the possibility of the two parties benefiting from each other, strengthening the the universities’ relationship with private sector institutions, and implementing joint quality research projects between universities and private sector institutions in order to achieve the Kingdom’s 2030 vision.